Hospital and Clinic Location Search System Based on Android with a Combination of GPS Systems - Jeprianto Jeprianto; Dika Adi Pratama (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
From the analysis obtained there is a need for sufficient availability of media effective in introducing the locations of hospitals and clinics in the Pringsewu district. The purpose of this paper is to produce an android application that can facilitate the community in finding information about the location of hospitals and clinics in the Pringsewu district. This application is an android platform. This application utilizes the global positioning system in user position search. The main facilities contained in this application are the map feature and road routes that can facilitate users in finding the destination location. The methodology used to build the application is the method of observation, interviews, and literature. While the system development used is the waterfall, this stage begins with needs analysis, system design, coding, testing. This application was developed with the concept of guiding hospital information and clinics based on android using GPS and maps to determine the distance traveled.